RELATIONAL PARADIGM OF LIFE NEW MEANINGS AND VALUES FOR LIFE WHEN VIRUSES THREATEN - Medina, Alice Maria Corrêa (Revista da FUNDARTE, 2021)
Observing the new coronavirus pandemics context currently traversed by humanity, it is possible to broadly and safely assess the distance between human beings and the environment in terms of the perception, reading, and understanding of nature within their ecosystems and environments. The promotion of debates and considerations on the production of meanings for life, based on human and environmental relations, can be considered as an important strategy for the creation of common bonds, thus displaying the need for a change in mainstream logic for a more organic relationship between humanity and the environment.